Edge-sited Fe-N4 atomic species improve oxygen reduction activity via boosting O2 dissociation - Ma, Ruguang; Lin, Gaoxin; Ju, Qiangjian; Tang, Wei; Chen, Gen; Chen, Zhenhua; Liu, Qian; Yang, Minghui; Lu, Yunfeng; Wang, Jiacheng (Applied catalysis. B, Environmental, 2020)
[Display omitted] Porous carbons with edge-sited Fe-N4 species were successfully prepared from Fe-containing abundant biomass, which shows superior electrocatalytic oxygen reduction performance, as well higher power/energy density and stability than commercial Pt/C in Zn-air battery. The theoretical calculations indicate that O2 molecule adsorbs on edged Fe-N4 sites with an energetically favorable side-on configuration with elongated OO bond, boosting the subsequent dissociation pathway with a direct 4e− reaction route. •Edge-sited Fe-N4 atomic species are formed by pyrolysis of abundant Fe-containing biomass.•The microstructures of Fe-N4 species are revealed by advanced HAADF-STEM, XANES, and Mössbauer techniques.•The ORR activity of edge-sited Fe-N4 species is promoted by elongating OO bond.•The Zn-air battery using edge-sited Fe-N4 species shows a high specific capacity and power density as well as long-life over 200 h.•The density functional calculations are employed to explain the origin of improved activity from the electronic structure. The development of low-cost, efficient, and stable electrocatalysts toward the oxygen reduction reaction (ORR) is urgently demanded for scalable applications in fuel cells or zinc-air batteries (ZABs), but still remains a challenge. Herein, carbon materials with edge-sited Fe-N4 atomic species (E-FeNC) were synthesized from pyrolysis of abundant Fe-containing biomass using silica spheres as hard template. The E-FeNC delivers remarkable ORR performance with a half-wave potential of 0.875 V (vs. reversible hydrogen electrode (RHE)), much better than Pt/C (0.859 V), attributed to atomically dispersed Fe-N4 moieties nearby graphitic edges. The density functional calculations reveal that O2 molecule adsorbs on Fe-N4 sites with an energetically favorable side-on configuration with elongated OO bond rather than end-on form, boosting the subsequent dissociation pathway with a direct 4e reaction route. Using E-FeNC as cathode catalyst, the primary ZAB exhibits high specific capacity of 710 mA h g−1 and power density of 151.6 mW cm−2. The rechargeable ZAB by coupling E-FeNC and NiFe layered double hydroxide (LDH) demonstrates long-term capacity retention over 200 h, superior to that using noble Pt/C and RuO2. This unique carbon material with atomically dispersed metal sites opens up an avenue for the design and engineering of electrocatalysts for energy conversion systems.